Development of Comic-Based Biology Learning Materials on the Topic of Motion Systems in Humans - Firzanah, Nurin; Rasyida, Rasyida (Jurnal Pendidikan MIPA, 2023)
This research aims to develop comic-based learning media that is appropriate, practical and effective to use. This development research used the ADDIE development model, consisting of five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique used is a combination of qualitative and quantitative. Based on the results of the validation of material experts, the assessment achieved an average of very decent with a percentage of 92.8% in the subject matter expert section 1 while the material expert 2 received a score of 100%. Based on the results of media expert validation, the average rating achieved was very feasible with a percentage of 96.4%. Based on the results of the questionnaire sheet, it gets a practicality value of 90.00% in the very practical category. Moreover, the N-Gain result is 0.60 in the medium category. It can be concluded that comic media is effectively used in the learning process with moderate effectiveness and is considered very practical.Keywords: learning materials, comics, biology learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp114-123